Pediatric Isolated Sinonasal Schwannoma: A New Case Report and Literature Review - Xiao-Hui Ma; Hai-Chun Zhou; Can Lai; Kun Zhu; Xuan Jia (Case Reports in Medicine)
Schwannomas of the paranasal sinus are uncommon. Less than 4% of schwannomas involve the nasal cavity and paranasal sinuses, even less in the pediatric age group. A case of schwannoma arising in maxillary sinus in a 2.5-year-old Chinese boy is reported. The basis for discussion of this case is the exceptional rarity of sinonasal schwannoma in pediatric patients.